The Nordstrom way of survival - Spector, Robert (Henry Stewart Talks, 2022)
About Nordstrom, How did Nordstrom survive the Covid-19 pandemic, Communication as a survival tool, Adapting physical and digital stores during the pandemic, Nordstrom and Amazon